Americanism : New Perspectives on the History of an Ideal - McCartin, Joseph Anthony; Kazin, Michael, 1948- (Book collections on Project MUSE., 2006)
What is Americanism? The contributors to this volume recognize Americanism in all its complexity--as an ideology, an articulation of the nation's rightful place in the world, a set of traditions, a political language, and a cultural style imbued with political meaning. In response to the pervasive vision of Americanism as a battle cry or a smug assumption, this collection of essays stirs up new questions and debates that challenge us to rethink the model currently being exported, too often by force, to the rest of the world.